LET'S GET PHYSICAL: A CONTEMPORARY REVIEW OF THE ANXIOLYTIC EFFECTS OF EXERCISE FOR ANXIETY AND ITS DISORDERS. Issue 4 (8th January 2013) - Asmundson, Gordon J. G.; Fetzner, Mathew G.; DeBoer, Lindsey B.; Powers, Mark B.; Otto, Michael W.; Smits, Jasper A. J.
<x xml:space="preserve">Abstract</x> Research over the past few decades has focused on the therapeutic effects of physical exercise among those affected by mood disorders. Only recently has attention turned to maladaptive and persistent expressions of anxiety, with a growing body of evidence indicating promise for exercise as an effective treatment for some of the anxiety disorders. The current review provides a comprehensive account of contemporary research examining the anxiolytic effects of exercise for anxiety disorders. We synthesize pertinent research regarding the effects of various types of exercise within the different anxiety disorders, consider impact of various types of exercise regimens on anxiety, and examine potential anxiolytic mechanisms responsible for positive mental health gains. We conclude with important considerations for implementing exercise as a treatment for clinically significant anxiety as well as future research directions.